2008
DOI: 10.1586/17446651.3.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Biotin and biotinidase deficiency

Abstract: Biotin is a water-soluble vitamin that serves as an essential coenzyme for five carboxylases in mammals. Biotin-dependent carboxylases catalyze the fixation of bicarbonate in organic acids and play crucial roles in the metabolism of fatty acids, amino acids and glucose. Carboxylase activities decrease substantially in response to biotin deficiency. Biotin is also covalently attached to histones; biotinylated histones are enriched in repeat regions in the human genome and appear to play a role in transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 104 publications
0
75
0
7
Order By: Relevance
“…The carboxylase activities decrease substantially when there is biotin deficiency. 8 The etiology of biotin deficiency is believed to be caused by a genetic defect in the transporter system of biotin across the bloodbrain barrier. 1 In 2005, it was demonstrated that homozygous mutation in SLC19A3 is the genetic defect that causes BBGD.…”
mentioning
confidence: 99%
“…The carboxylase activities decrease substantially when there is biotin deficiency. 8 The etiology of biotin deficiency is believed to be caused by a genetic defect in the transporter system of biotin across the bloodbrain barrier. 1 In 2005, it was demonstrated that homozygous mutation in SLC19A3 is the genetic defect that causes BBGD.…”
mentioning
confidence: 99%
“…La biotinidasi libera la vitamina biotina dalla sua forma legata e la rende disponibile; se l'enzima manca la vitamina è perduta [7,8]. Questo deficit impedisce alle cellule di utilizzare in modo efficiente la biotina con conseguenze di diversa gravità (acidosi chetolattica, aciduria organica, iperammoniemia, rash cutanei, ipotonia, convulsioni, ritardo nella crescita, alopecia), ma si può arrivare al coma e alla morte.…”
Section: Il Principiounclassified
“…El diagnóstico tardío o tratamiento inadecuado en etapas tempranas de la vida puede llevar a desarrollar daños neurológicos irreversibles, tales como retraso en el desarrollo y autismo. 2 Por el contrario, un diagnóstico temprano y tratamiento adecuado con administración de 5 a 10 mg por día indicado de por vida tanto en las formas de deficiencia profunda como parcial tiene una evolución favorable. Los pacientes detectados por tamizaje neonatal deberían permanecer asintomáticos de por vida si el tratamiento con biotina es precoz y sostenido continuamente.…”
Section: Figura 3 Angiotomografía De Corazón Posterior a La Cirugíaunclassified